MAKNA PADA NOVEL LIMITLESS KARYA NADHIRA AFIFA (TINJAUAN SEMIOTIK ROLAND BARTHES) - Andi Nur Hikmah Hakim Petta Bau; La Ode Syukur; La Yani Konisi (Jurnal Bastra (Bahasa dan Sastra), 2025)
This research aims to identify the forms of meaning based on semiotic lexicons according to Roland Barthes, using Roland Barthes' codes, as well as the use of these codes to uncover the meaning in the novel Limitless by Nadhira Afifa. The method used in this research is descriptive qualitative with a type of library research. The data source for this research is the novel Limitless by Nadhira Afifa, consisting of 232 pages, published by Mediakita in 2021. The data collection technique involves reading and taking notes, while the data analysis technique employs descriptive analysis. The novel Limitless by Nadhira Afifa depicts the sweet and bitter journey of Nadhira Afifa in achieving her dreams. Armed with hard work and a strong desire, Nadhira proves her abilities and successfully fulfills her dreams one by one. The result of this research seeks to find the meanings contained in the novel written by Nadhira Afifa through Roland Barthes' semiotic codes, which include five codes: hermeneutic code, connotative code, symbolic code, action code, and cultural code. The total amount of data reaches 72 pieces.